1997
DOI: 10.1109/84.623112
|View full text |Cite
|
Sign up to set email alerts
|

A fabrication process for electrostatic microactuators with integrated gear linkages

Abstract: A surface micromachining process is presented which has been used to fabricate electrostatic microactuators. These microactuators are interconnected with each other and linked to other movable microstructures by integrated gear linkages. The gear linkages consist of rotational and linear gear structures, and the electrostatic microactuators include curved electrode actuators, comb-drive actuators, and axial-gap wobble motors. The micromechanical structures are constructed from polysilicon. Silicon dioxide was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The pull-down behavior of the curved electrostatic actuators was a strong function of the initial curvature of the electrodes. It was shown by Legtenberg et al 12 that the second derivative of the total potential energy with respect to polynomial order, n, is negative for n р 2, indicating unstable behavior. The actuators with movable electrodes created by deposition of 0.1 m of hard gold showed an initial curvature of polynomial order 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pull-down behavior of the curved electrostatic actuators was a strong function of the initial curvature of the electrodes. It was shown by Legtenberg et al 12 that the second derivative of the total potential energy with respect to polynomial order, n, is negative for n р 2, indicating unstable behavior. The actuators with movable electrodes created by deposition of 0.1 m of hard gold showed an initial curvature of polynomial order 2.…”
Section: Discussionmentioning
confidence: 99%
“…10 The stable behavior of the electrostatic actuator can also be improved by incorporating curvature to the electrodes. Legtenberg et al 12 have shown that the pull-down behavior of the curved electrostatic actuator depends on the shape of the curved electrode. Stable behavior with relatively large displacements and forces can be generated by curved electrodes where curvature with length can be described by a polynomial order greater than 2.…”
mentioning
confidence: 99%
“…A simple description of diffusion is given by Fick's laws: the molar flux due to diffusion is proportional to the concentration gradient. This can be described by the following formula [31]:…”
Section: The Principle Of Cfsmentioning
confidence: 99%
“…The CFS method can avoid the formation of a liquid-air interface as well as the influence of surface tension. The cyclohexane solution with a phase transition temperature of 6.5 °C and low surface tension is chosen as the medium in the CFS method [30][31][32]. Nitrogen gas was introduced to increase the surface convection and sublimation rate of solid cyclohexane.…”
Section: Introductionmentioning
confidence: 99%
“…la). For example, the micro x-y-z stage carrying an STM tip [2], the vibrating gyroscope [3] or the micro-gear [4] are all MEMS with several mechanical components interacting with each other in the plane of the wafer.…”
Section: Introduction: In-plane Dof Vs Out Of Plane Dofmentioning
confidence: 99%